Analysis Of The Influence Of Marketing And Communications Consumer Loyalty Towards Decisions Buy Products At PT. Kingled Indonesia Medan - Agusman, Agusman; Sofyan, Silvia; Robin, Robin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
This research aims to determine the influence of marketing communications and consumer loyalty towards the decision to buy products at PT Kingled Indonesia. The data collection method uses a questionnaire. The questionnaire has been tested validity and reliability before collecting research data. Data analysis The technique in this research uses classical and multiple linear assumption tests regression analysis. The research results show that marketing communications are partially positive and significant influence on purchasing decisions. This is proven by the tcount value of 4.024 > from ttable it is 1.661 and the significant value is below 0.1, namely 0.000. When Consumer loyalty partially has a positive and significant effect on purchasing decisions. This is proven by tcount of 3.801 > from ttable of 1.661 and a significant value below 0.1, namely 0.000. At the same time, marketing communications and Consumer loyalty has a positive and significant effect on purchasing decisions. This is proven by Fcount of 23.930 > Ftable 2.36 and is significant the value is below 0.1, namely 0.000. Meanwhile, the amount of influence given is 34.5%. The rest is influenced by other factors outside this research. This research aims to determine the influence of marketing communications and consumer loyalty towards the decision to buy products at PT Kingled Indonesia. The data collection method uses a questionnaire. The questionnaire has been tested